2018
DOI: 10.3390/molecules23123373
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Composition, Antioxidant Properties, and Inhibition toward Digestive Enzymes with Molecular Docking Analysis of Different Fractions from Prinsepia utilis Royle Fruits

Abstract: The present study investigated the phenolic profiles and antioxidant properties of different fractions from Prinsepia utilis Royle fruits using molecular docking analysis to delineate their inhibition toward digestive enzymes. A total of 20 phenolics was identified and quantified. Rutin, quercetin-3-O-glucoside, and isorhamnetin-3-O-rutinoside were the major phenolic compounds in the total phenolic fraction and flavonoid-rich fraction. The anthocyanin-rich fraction mainly contained cyanidin-3-O-glucoside and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 52 publications
1
52
0
2
Order By: Relevance
“…Hua et al (2018) have also reported that Asp 69, Asp 215, and Arg 442 were the important residues involved in H-bond formation during the binding with α-glucosidase [37]. also reported that the binding active sites (Asp 215 and Asp 352) in between the ligands and α-glucosidase played important roles in exert its α-glucosidase inhibitory effect [23]. Similarly, the order of amino acid residues numbers formed by four molecules (GA, EA, PC, and Acarbose) docked with α-amylase was: Acarbose (7) = PC (7) > GA (5) > EA (4).…”
Section: Molecular Docking Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Hua et al (2018) have also reported that Asp 69, Asp 215, and Arg 442 were the important residues involved in H-bond formation during the binding with α-glucosidase [37]. also reported that the binding active sites (Asp 215 and Asp 352) in between the ligands and α-glucosidase played important roles in exert its α-glucosidase inhibitory effect [23]. Similarly, the order of amino acid residues numbers formed by four molecules (GA, EA, PC, and Acarbose) docked with α-amylase was: Acarbose (7) = PC (7) > GA (5) > EA (4).…”
Section: Molecular Docking Resultsmentioning
confidence: 95%
“…The correlation analysis results between the TPC and two digestive enzymes inhibition potency clearly verified that there was a good positive correlation between these two parameters (α-glucosidase inhibition potency vs. TPC, r = 0.781, p < 0.05; α-amylase inhibition potency vs. TPC, r = 0.854, p < 0.01). Many researches have confirmed that phenolic-rich extracts from leaf-tea, edible fruits, and natural products possess good inhibitory ability on digestive enzymes [23,37]. have confirmed that procyanidin C3 possessed strong α-glucosidase inhibitory capacity [38].…”
Section: Type II Diabetes Related Enzymes Inhibitory Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Esto concuerda con el análisis de docking realizado para el pNPL (Figura 4a). Mientras que el sitio para RUT, diferente al del resto de los flavonoides, se encuentra ubicado en una región comprendida entre el sitio activo y la colipasa (Zhang et al, 2018). La inhibición mixta observada para la mayoría de los flavonoides, indica que los flavonoides se unen al enzima antes y después de que el sustrato esté unido (Birari et al, 2011;Li et al, 2011).…”
Section: Análisis De Las Interacciones Lipasa-flavonoides Mediante Dounclassified
“…La estructura plana del anillo C de LUT y QUE les permite ingresar e interactuar con los residuos de aminoácidos del sitio activo (Cerezo et al, 2015). En este sentido, la mayoría de los flavonoides interactúan con el subsitio 1 (mayor actividad) de los tres sitios descritos por otros autores, y RUT con el subsitio 3, ambos hidrofóbicos (Zhang et al, 2018). Se señala que el Orlistat se une a los tres subsitios e impide el ingreso del sustrato.…”
Section: Análisis De Las Interacciones Lipasa-flavonoides Mediante Dounclassified